PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI BERBASIS PROJECT BASED LEARNING PADA MATERI VIRUS TERHADAP HASIL BELAJAR KOGNITIF DI SMA MUHAMMADIYAH 1 JOMBANG - Mufaridha, Lailatul; Rahardjanto, Abdulkadir; Purwanti , Elly; Susetyarini, Roro Eko; Husamah; Hudha, Atok Miftachul; Dita Tri Mulyani (Jurnal Biogenerasi, 2025)
Virus-related materials can be challenging to comprehend due to its use of scientific and abstract terminology that is often difficult to visualize or directly observe. This difficulty is evident among students at SMA Muhammadiyah 1 Jombang, particularly when learning about the classification and types of viruses. The challenges students face in understanding this material are reflected in their cognitive learning outcomes, which have not yet reached the minimum completeness standard. On average, students' scores are 68, which falls under the "below average" category. This issue arises because the learning modules currently used in the classroom are limited to school textbooks, which do not adequately cover the subtopics of virus classification and types. As a result, there is a pressing need to support active learning by developing PjBL-based biology learning modules that are more accessible and easier for students to understand. The aim of this study was to determine the implementation of Project Based Learning (PjBL) based learning modules on virus material on cognitive learning outcomes. The experimental class has a corrected mean score of 50.112. Similar result is obtained in the control class with a corrected mean score of 46.415. Thus, the PjBL-based Biology module does not show any potential in improving cognitive learning outcomes.